Impact of parathyroid gland classification on hypoparathyroidism following total thyroidectomy with central neck dissection for differentiated thyroid cancer - Qixuan Sheng; Wei Li; Ping Zhang; Qiang Wang; Siluo Zha; Wensheng Rao; Bin Wang; Xinyun Xu; Ming Qiu; Wei Zhang; Chengxiang Shan (Annals of Medicine)
Objective To assess the impact of parathyroid gland (PG) classification on hypoparathyroidism incidence following total thyroidectomy (TT) with central neck dissection (CND) in patients with differentiated thyroid carcinoma (DTC).Methods In this prospective cohort study, adult patients with DTC who underwent TT with CND between 2021 and 2023 were enrolled, with a maximum follow-up duration of 32 months. A simplified PG classification system was employed, categorizing glands into four distinct types: tightly connected, loosely connected, non-connected, and thymic. The intraoperative frequency of each PG type was recorded based on this classification. Parathyroid hormone (PTH) levels were routinely tested 1 day, 1 month, 6 months and 1 year after surgery. The association between PG classification and the incidence of postoperative hypoparathyroidism was then systematically analysed.Results Among 135 patients with DTC (mean age: 48.50 ± 10.52 years; 101 women), 62 patients (45.93%) developed hypoparathyroidism on postoperative day 1 (POD1), while 14 patients (10.37%) experienced hypoparathyroidism on postoperative month 1 (POM1). All patients exhibited PTH normalization within six months, with no permanent hypoparathyroidism cases. A total of 532 PGs were identified: 264 (49.62%) were tightly connected, 150 (28.20%) loosely connected, 95 (17.86%) non-connected, and 23 (4.32%) thymic. The highest prevalence of hypoparathyroidism on POD1 was observed in patients with four tightly connected PGs (p < 0.001). Patients with four tightly connected PGs had a significantly greater incidence of hypoparathyroidism than those with none (p = 0.024). Regression analysis revealed that each additional tightly connected PG increased the risk of hypoparathyroidism by 1.38 times (p = 0.019). Tightly connected PGs demonstrated predictive value for POD1 hypoparathyroidism (AUC = 0.604, cut-off: two tightly connected glands). In contrast, thymic PGs did not provide a protective effect.Conclusion PG classification may serve as a valuable tool for surgeons in intraoperative parathyroid preservation and the prediction of postoperative hypoparathyroidism in patients with DTC. Notably, DTC patients with more than two tightly connected PGs are at an elevated risk of developing temporary hypoparathyroidism, emphasizing the importance of meticulous parathyroid preservation during surgical procedures.